The Government's Role in Improving MSME Business Performance in Denpasar City - Arjawa, I Gde Wedana; Made Pulawan, I; Ayu Sita Laksmi, Putu (Dinasti Publisher, 2025)
This study aims to analyze the role of the government in improving the business performance of MSMEs in Denpasar City. Using a quantitative approach and data collection method through questionnaires, this study involved 100 MSME respondents from a population of 32,626. The results of data analysis using Structural Equation Modeling (SEM) show that the role of the government, measured through regulations, access to financing, and training programs, has a positive and significant influence on the business performance of MSMEs. These findings emphasize the importance of government intervention in creating an environment conducive to the growth of MSMEs. In addition, this study identifies the challenges faced by MSMEs in accessing government support, as well as providing recommendations for policymakers to improve the effectiveness of existing programs. Thus, this research contributes to the development of public policies that are more responsive to the needs of MSME actors in Denpasar City.